SMYD1 is the underlying gene for the AnWj‐negative blood group phenotype. (3rd August 2018) - Yahalom, Vered; Pillar, Nir; Zhao, Yingying; Modan, Shirley; Fang, Mingyan; Yosephi, Lydia; Asher, Orna; Shinar, Eilat; Celniker, Gershon; Resnik‐Wolf, Haike; Brantz, Yael; Hauschner, Hagit; et al.
Abstract: Background: AnWj is a high‐incidence blood group antigen associated with three clinical disorders: lymphoid malignancies, immunologic disorders, and autoimmune hemolytic anemia. The aim of this study was to determine the genetic basis of an inherited AnWj‐negative phenotype. Methods: We identified a consanguineous family with two AnWj‐negative siblings and 4 additional AnWj‐negative individuals without known familial relationship to the index family. We performed exome sequencing in search for rare homozygous variants shared by the two AnWj‐negative siblings of the index family and searched for these variants in the four non‐related AnWj‐negative individuals. Results: Exome sequencing revealed seven candidate genes that showed complete segregation in the index family and for which the two AnWj‐negative siblings were homozygous. However, the four additional non‐related AnWj‐negative subjects were homozygous for only one of these variants, rs114851602 (R320Q) in the SMYD1 gene. Considering the frequency of the minor allele, the chance of randomly finding 4 consecutive such individuals is 2.56 × 10 −18 . Conclusion: We present genetic and statistical evidence that the R320Q substitution in SMYD1 underlies an inherited form of the AnWj‐negative blood group phenotype. The mechanism by which the mutation leads to this phenotype remains to be determined.